Sensing Boundaries on Foot. Experiencing Limits of Mobility through Nineteenth Century European Art. - Idrobo Carlos (Finland, 2022)
This article examines the material and socio-cultural mechanisms by which everyday urban and rural walking is controlled, regulated, limited, or affected, as seen through the lens of nineteenth century visual arts with support of literary and historical accounts. Inspired by the interdisciplinary research on walking, I discuss three cases of different cultural and historical backgrounds and examine therein the instances in which the experience of walking cannot fully take place, or its movements are shaped or controlled by real or imaginary forces, either external or internal, or even by other modes of transportation: 1) C. G. Carus’ socially constrained travelling in Italy in 1828, leading up to his painting Erinnerung an Neapel, 2) the history of the Pont Neuf and the use and regulation of Paris footways through lithographs and ‘impressionist’ paintings in the Third Republic, and 3) the motif of the ‘riukuaita’ (round-pole fence) in lithographs, landscape paintings and photographs during the Golden Age of Finnish Art. Thus, art objects are considered as both artworks and historical documents that illuminate the imaginary and actuality of historical events related to migration, bordering processes, and control of mobility.